Fabrication of Improvised Dye-Sensitized Solar Cells from Mangosteen Pericarp Extract (Philippine Journal of Agricultural Economics, 2019)
Recent researches are geared towards finding alternative sources of renewable energy and solar power seems to be an attractive avenue and currently, dye-sensitized solar cells (DSSC) have gained worldwide attention. This study aimed to fabricate DSSC that makes use of an improvised conductive glass, with zinc oxide in nappy cream as photoanode and mangosteen pericarp extract as a sensitizer. It sought to find the effect of DSSC processing on the conductivity and performance in terms of current, voltage, and power density generated, and evaluate its stability. Ordinary 1/8" mirror was made conductive glass by stripping the gray coat with very fine sandpaper then heating to remove the orange coat. Conductivity was good (2.1 ohms) and etching with povidone-iodine provided transparency for the photoanode. The DSSCs were capable of producing a mean current of 0.0007 mA and mean voltage of 2.8670 mV that last for ninety minutes. The present study showed DSSCs could be constructed using indigenous materials. Further research is needed for finding ways to improve its efficiency and lifespan. By knowing the principles of the DSSCs, and enhancing the innovativeness and creativity of the current DSSC, researchers can overcome the lack of expensive materials and equipment for future studies.